A Study on Development of Main Character and Characterization in “Bohemian Rhapsody” Movie - Sardiana, Gerdi Kafi Lole; Utami, Ni Made Verayanti; Ariyaningsih, Ni Nyoman Deni (Journal of Language and Applied Linguistics, 2024)
There are two objectives of the study the first one is to identify the main character development in the “Bohemian Rhapsody” movie. the second is to analyze characterization of the main character in “Bohemian Rhapsody” movie. The data of this study were taken from the movie entitled Bohemian Rhapsody. The data source in this study was take from the movie in the movie was analyzed descriptively based on the theory How To Analize Fiction proposed by William Kenney (1956). The main character development was analyzed into two categorizes which is simple(flat) character and complex(round) characters. The characterization of the main character was analyzed into three categorize which is physiological, sociological, and psychological dimension of the main characterization. The characterization of Freddie Mercury over all is that he is a kind person, humble, gentle and romantic person but in the middle of the story he changed into a bad person, ego and unfriendly person which make him a complex(round) character.